Towards universal health coverage: mapping the development of the faith-based non-profit sector in the Ghanaian health system - Grieve, Annabel (Department of Public Health and Family Medicine, 2018)
The equitable provision of accessible quality health services and the achievement of universal health coverage (UHC) continue to be prominent on the global health agenda, yet remains an elusive target for many low- and middle-income countries (LMIC). In these contexts, the private not-for-profit (PNFP) sector plays a significant role, and in many African countries, faith-based non-profit (FBNP) providers dominate this sector. Robust public-private partnerships are increasingly being recognised as important to building and maintaining strong, resilient health systems. However, there is a lack of evidence on whether collaborations between FBNPs and the public sector are complementary, have achieved their intended aims, or exactly how these relationships developed over time to shape these health systems. Furthermore, reliable information on both the historical and current spatial distribution of services and how this relates to geographic accessibility and the achievement of UHC is limited. This study explores this in Ghana, a country with a large FBNP sector, mostly networked under the Christian Health Association of Ghana (CHAG) which has an influential and now formalised relationship with the government. The following health systems research study utilises a mixed methods approach, synthesising geospatial mapping with varied documentary resources (secondary and primary, current and archival). The evolution of the FBNP sector and the shifts in service footprint are reflected in the geospatial maps, aligned with key historical events and contextualised by a narrative analysis. The study highlights that many faith-based facilities were initially located in rural and remote areas beyond colonial governance control (or boundaries), and many of these facilities still exist, demonstrating resilience to change over time. However, this service footprint has changed and today, public and private health facilities are located in similar areas throughout the country. This trend is in-line with social and political events, changing population dynamics and an increasing population of urban poor. The analysis assesses how the growth of the public sector, and these shifts in presence and profile for the FBNPs has influenced their perceived and measured contribution to UHC - in particular geographic accessibility. This study provides a model for representing the evolution of the relationship between public and a particular type of non-state provider over time, characterising the historical development of the health system, which should be considered in efforts to strengthen and develop the Ghanaian health system, and other relatable LMIC health systems.